Level of Competence Among Selected Sangguniang Kabataan Officials in Utilizing Accounting System for Transparent and Good Financial Management (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The primary goal of the study was to determine the level of competence among selected Sangguniang Kabataan officials in Mogpog, Marinduque, in utilizing the accounting system for transparent and good financial management. More specifically, it aimed at evaluating their skills in preparing budgets, recording and bookkeeping, reporting, and digital accounting software. The study further gave an account of the main difficulties as well as the financial training practices that the respondents thought would elevate their financial skills. A descriptive research design and survey methods were employed in the study to gather data from 60 SK officials representing the different neighborhoods of Mogpog. The outcomes showed that the corresponding groups of people had an overall competency level from moderate to high, and the area of their highest proficiency was budget preparation and record keeping. Whereas the SK officials' inability to timely report and use digital tools for accounting was pointed out as their weakness areas, mainly caused by a lack of experience and complicated government regulations. The areas identified for training needs in the future were Basic Bookkeeping and Financial Recording. The conclusion reached by the researcher was that training, mentoring, and the application of technology should be the key to the development of SK officials' financial management skills. It was also pointed out that the local government, along with the Commission on Audit (COA) and the Department of the Interior and Local Government (DILG) could facilitate regular workshops, hands-on simulations, and institutionalized training that would be professionally supported by these organizations. The investment in the accounting skills of the SK officials will help them in being the custodians of transparency, accountability, and efficiency in public fund management, thus paving the way for a more trusted and effective youth governance.